WADAH AKTIVITAS SENI DIGITAL DAN KERAJINAN - Wandy Wandy; Dewi Ratnaningrum (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The development of science and information technology caused major changes in this era. One of them is in everyday human activities. The number of micro communities based on expertise and ability has emerged and formed by itself and started to be called upon by the younger generation. Until now the knowledge and interest of the community about the creative industry still cannot be accommodated and the cultural needs that have occurred have changed. Another thing that happens is that the gap between the forms of work carried out by the younger generation is based on interests and hobbies that are loved so that the level of productivity also increases. One sector that is still minimal and has a high community level is craft. Crafts are one of the sectors that have a large role in the creative economy and are used to preserve local cultural values. Therefore, in helping the development and creative economic growth and answering these challenges, one alternative is to create a Digital Art and Craft Makerspace project. By using the field survey method and typology, it is expected that the project can become a forum for the community, especially the younger generation and local residents. The relationship between container activities and human resources has an important role. The purpose of Digital Art and Craft Space is to attract young people to be able to channel their interests and talents with the form of training and adequate information needs so that they can be creative in expressing ideas or ideas whose end results have cultural values. AbstrakPerkembangan ilmu pengetahuan dan teknologi informasi menyebabkan perubahan besar di era ini. Salah satunya adalah pada aktivitas manusia sehari-hari. Jumlah komunitas mikro yang berdasarkan keahlian dan kemampuan telah muncul dan terbentuk dengan sendirinya serta mulai diserukan oleh para generasi muda. Hingga saat ini pengetahuan dan minat masyarakat tentang industri kreatif masih belum dapat terwadahi dan kebutuhan budaya yang terjadi telah berubah. Hal lain yang terjadi adalah kesenjangan antara bentuk pekerjaan yang dilakukan oleh para generasi muda adalah berbasis minat dan hobi yang disenangi sehingga membuat tingkat produktivitas juga meningkat. Salah satu sektor yang masih minim dan memiliki tingkat komunitas tinggi adalah kerajinan. Kerajinan merupakan salah satu dari sektor yang memiliki peran besar dalam ekonomi kreatif dan guna untuk pelestarian nilai-nilai budaya lokal. Oleh karena itu, dalam membantu perkembangan dan pertumbuhan ekonomi kreatif dan menjawab tantangan tersebut maka salah satu alternatif adalah dengan membuat proyek Digital Art and Craft Makerspace. Dengan menggunakan metode survei lapangan, dan tipologi maka diharapkan  proyek dapat menjadi wadah bagi masyarakat khususnya kaum generasi muda dan penduduk lokal. Hubungan antara wadah kegiatan dan sumber daya manusia memiliki peranan penting. Tujuan Digital Art and Craft Makerspace dibangun adalah untuk menarik para generasi muda untuk dapat menyalurkan minat dan bakat mereka dengan bentuk pelatihan dan kebutuhan informasi yang memadai agar dapat berkreasi dalam menuangkan ide atau gagasan yang hasil akhirnya memiliki nilai budaya.